Changes in blood lymphocyte numbers with age in vivo and their association with the levels of cytokines/cytokine receptors. Issue 1 (December 2016) - Lin, Yun; Kim, Jiewan; Metter, E.; Nguyen, Huy; Truong, Thai; Lustig, Ana; Ferrucci, Luigi; Weng, Nan-ping
Abstract Background Alterations in the number and composition of lymphocytes and their subsets in blood are considered a hallmark of immune system aging. However, it is unknown whether the rates of change of lymphocytes are stable or change with age, or whether the inter-individual variations of lymphocyte composition are stable over time or undergo different rates of change at different ages. Here, we report a longitudinal analysis of T- and B-cells and their subsets, and NK cells in the blood of 165 subjects aged from 24 to 90 years, with each subject assessed at baseline and an average of 5.6 years follow-up. Results The rates of change of T-(CD4+ and CD8+ ) and B-cells, and NK cells were relative stable throughout the adult life. A great degree of individual variations in numbers of lymphocytes and their subsets and in the rates of their changes with age was observed. Among them, CD4+ T cells exhibited the highest degree of individual variation followed by NK cells, CD8+ T cells, and B cells. Different types of lymphocytes had distinct trends in their rates of change which did not appear to be influenced by CMV infection. Finally, the rates of CD4+, CD8+ T cells, naive CD4+ and naïve CD8+ T cells were closely positively correlated. Conclusion Our findings provide evidence that the age-associated changes in circulating lymphocytes were at relative stable rates in vivo in a highly individualized manner and the levels of selected cytokines/cytokine receptors in serum might influence these age-associated changes of lymphocytes in circulation.